2021
DOI: 10.3389/fpubh.2020.603005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Epidemiology of Salmonellosis in Florida, 2009–2018

Abstract: Non-typhoidal Salmonella enterica infections cause a high disease burden in the United States with an estimated 1.2 million illnesses annually. The state of Florida consistently has a relatively high incidence compared to other states in the United States. Nevertheless, studies regarding the epidemiology of nontyphoidal salmonellosis and its spatial and temporal patterns in Florida were rarely reported. We examined the spatial and temporal patterns of 62,947 salmonellosis cases reported to FL Health Charts bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
3
15
0
2
Order By: Relevance
“…We present a retrospective analysis of whole genome sequencing data of Salmonella enterica isolates from Florida in the years 2017-2018. Our earlier work has shown that the sequenced isolates in 2017-18 were a relatively unbiased sample of confirmed clinical cases (4). The population structure of Salmonella is Florida was found to be highly diverse with 115 serotypes observed in a set of 1,632 sporadic clinical isolates obtained over this 2-year period.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We present a retrospective analysis of whole genome sequencing data of Salmonella enterica isolates from Florida in the years 2017-2018. Our earlier work has shown that the sequenced isolates in 2017-18 were a relatively unbiased sample of confirmed clinical cases (4). The population structure of Salmonella is Florida was found to be highly diverse with 115 serotypes observed in a set of 1,632 sporadic clinical isolates obtained over this 2-year period.…”
Section: Discussionmentioning
confidence: 94%
“…Metadata Collection and ManagementAn integrated and deidentified metadata set from BPHL Bionumerics and FDOH Merlin database was made available by FDOH under a data sharing agreement, details are provided in Li et al(4). We selected isolates from metadata received from FDOH, with a date of sample collection by the clinical laboratory from January 2017 to December 2018 and downloaded sequence data from Enterobase (https://enterobase.warwick.ac.uk) using PNUSA numbers specified in the metadata (https://dataverse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serotype prediction was performed in the EnteroBase online server (https://enterobase.warwick.ac.uk/) [19] as described in [6]. We included the top five Salmonella serotypes in Florida, plus two additional serotypes, Typhimurium and I 4, [5],12:i:-(a monophasic variant of Typhimurium), that are on the list of top five serotypes across the whole USA (Table 1).…”
Section: Serotype Predictionmentioning
confidence: 99%
“…Some serotypes are mainly transmitted by food, such as the serotypes Saintpaul, Heidelberg and Berta, but others such as Bareilly and Mississippi appear to be less linked to food pathways [8]. The five most common serotypes identified through the FoodNet surveillance system in the USA are Enteritidis, Typhimurium, Newport, Javiana and I 4, [5],12:i:-, a monophasic variant of Typhimurium [9], while the major serotypes occurring in Florida are Enteritidis, Newport, Javiana, Sandiego and Braenderup [6]. In our previous work, we conducted a phylogenetic analysis of Salmonella isolates from five dominant serotypes in Florida and identified the geographical distribution of clusters of genetically related isolates using core genome multi-locus sequence typing (cgMLST), a subtyping approach that provides high resolution to distinguish isolates within the same serotype [10].…”
Section: Introductionmentioning
confidence: 99%